2003
DOI: 10.1210/en.2003-0485
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Genes Differentially Expressed in Dominant and Subordinate Bovine Follicles

Abstract: In monoovulatory species such as cattle, unknown mechanisms lead to the selection of one of a cohort of developing ovarian follicles to assume dominance and continue to grow in each follicular wave. We have used suppressive subtraction hybridization to identify genes differentially expressed in the granulosa cells of dominant and subordinate follicles. Inhibin beta A, apolipoprotein E receptor 2, MAPK kinase kinase 5 (ask1), and carboxypeptidase D were isolated and verified to be reliable markers for dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Thus, it may be possible to imagine that the dominant and subordinate follicles have unique molecular signals that may affect differently the bidirectional crosstalk between the oocytes and the granulosa cells. Although, several authors [10][14] have described the presence of altered gene expression patterns in theca and/or granulosa cells of different follicular stages, the post transcriptional gene expression regulation mechanisms that lead the follicle to become dominant or subordinate are still unclear. Here we investigated accumulation or degradation of miRNAs in granulosa cells of subordinate and dominant follicles during the early luteal phase of the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it may be possible to imagine that the dominant and subordinate follicles have unique molecular signals that may affect differently the bidirectional crosstalk between the oocytes and the granulosa cells. Although, several authors [10][14] have described the presence of altered gene expression patterns in theca and/or granulosa cells of different follicular stages, the post transcriptional gene expression regulation mechanisms that lead the follicle to become dominant or subordinate are still unclear. Here we investigated accumulation or degradation of miRNAs in granulosa cells of subordinate and dominant follicles during the early luteal phase of the estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to the hypothesis that the follicular microenvironment could have unique molecular signals which would affect differently the bidirectional crosstalk between the oocytes and the companion somatic cells in the subordinate and dominant follicles. In this regard, several signaling molecules including the TGF-beta superfamily members, follicle stimulating hormone receptor, luteinizing hormone receptor, cytochrome 450s (CYP11A1, CYP17A1, CYP19A1) , GDF9, IGF-1, IGF-II, IGFBP2 and several of genes have been found to be altered in granulosa and/or theca cells depending on the size and stage of follicular development [10][14]. Abnormal expression of those developmentally related genes and gene products in the oocytes and supporting cells could then lead to cellular communication dysfunction and dysregulation of normal follicle recruitment and development [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent attempts to identify genes that regulate the selection and recruitment of follicles to develop into mature oocytes during the bovine estrous cycle by expression profiling led to the identification of ApoER2 as a candidate for such a function (10,11). In another study, ApoER2 has been shown to be preferentially expressed in bovine dominant follicles when compared with subordinate follicles (12). A splice variant of VLDLR, which is the major player in yolk uptake by the oocyte, is also expressed in chicken granulosa cells (13).…”
mentioning
confidence: 99%
“…In the last decade, rapid progress has been made in discovering key players in these processes by using molecular techniques such as differential mRNA display (6,7), subtraction hybridization (8,9), ovarian cDNA library screening (10), and DNA microarray (11)(12)(13). Results from these pioneering studies have reinforced the belief that follicular development and ovulation are highly complex, tightly regulated processes that require numerous hormone-induced factors.…”
mentioning
confidence: 99%